PENGGUNAAN MEDIA COLOR-CODED SHAPE CARDS PADA MATERI BANGUN DATAR UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SD - Restu Putpitasari, Devi; Bintartik, Lilik; Surya Kinasih, Aldi; Tazky Amalia, Alviena; Suaidah, Amida; Relung Puspita, Hinggar; Kiswoyo Putri, Sinta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted with the aim of improving the critical thinking skills of fourth-grade elementary school students through the use of Color-Coded Shape Cards for the topic of geometric shapes. This research employs a Classroom Action Research (CAR) approach conducted over three cycles, with each cycle comprising the stages of planning, action implementation, observation, and reflection. Data were collected through media validation sheets and observation of teacher activity, student activity, and students' critical thinking skills. Data indicate that the media is highly suitable, with a rating of 93%, and students' critical thinking skills improved from 71% in Cycle I to 94% in Cycle III. Unlike previous studies that generally relied on card-based, geometric, or general visual media, this study offers a novelty by integrating a color-coding system as a cognitive cue that helps students identify relationships between plane figures. The findings indicate that Color-Coded Shape Cards media effectively supports mathematics learning that fosters students' critical thinking skills.